2006
DOI: 10.1007/s00381-005-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid shunt infection: risk factors and long-term follow-up

Abstract: Long-term follow-up of shunted children is necessary to evaluate the real incidence of SI and the functional outcome after SI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
4
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(148 citation statements)
references
References 20 publications
8
124
4
12
Order By: Relevance
“…This reaffirms that in these groups the suspicion of a shunt infection should be promptly investigated and treated. Gender does not seem to be a risk factor for developing a shunt infection 11,13,16 and there was no difference between the number of males and females infected (55% male, p=0.19) in our study. In our population 68% of infections occurred within nine months of shunt insertion and 59% within three months.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…This reaffirms that in these groups the suspicion of a shunt infection should be promptly investigated and treated. Gender does not seem to be a risk factor for developing a shunt infection 11,13,16 and there was no difference between the number of males and females infected (55% male, p=0.19) in our study. In our population 68% of infections occurred within nine months of shunt insertion and 59% within three months.…”
Section: Discussioncontrasting
confidence: 63%
“…Overall shunt infection rate in the UK is estimated at 5.2% 7 . Shunt infections have a mortality of 10.1% and worse Glasgow Outcome Scale scores, as well as worse school performance in the long-term 13 . From a public health perspective, shunt infections are associated with major hospital costs, with one episode costing approximately £29,000 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors including premature birth, occurrence of the first VPSI at a young age, congenital conditions such as meningomyelocele, post-hemorrhagic hydrocephalus, higher number of previous shunt infections, and the development of postoperative CSF leakage increase the risk of shunt infection (4,6,7,18,25). In this study, we found that children with VPSI in the first 3 months or with premature birth had a greater rate of shunt infections (high hospitalization coefficient) and higher treatment costs (high cost coefficient).…”
Section: Kanik a Et Al: Aspects Of Vps-related Infectionsmentioning
confidence: 56%
“…Although IV antibiotics are a mainstay of clinical practice in conjunction with surgery [13,24,25], duration of IV antibiotic use varies widely [14] and depends, in part, on the surgical approach used [1,26] and pathogen involved [25,27]. In previous studies, observed durations range from 9 days to 17 days [14,15,17].…”
Section: Discussionmentioning
confidence: 99%